Insights in the Study of the Oxygen Reduction Reaction in Direct Ethanol Fuel Cells using Hybrid Platinum-Ceria Nanorods Electrocatalysts - Pinheiro, Victor S.; Souza, Felipe M.; Gentil, Tuani C.; Böhnstedt, Paula; Paz, Edson C.; Parreira, Luanna S.; Hammer, Peter [UNESP]; Batista, Bruno L.; Santos, Mauro C. (Wiley, 2019)
This work reports on the synthesis and characterization of hybrid electrocatalysts based on Pt nanoparticles and ceria nanorods (CeO2 NR) supported on Vulcan XC-72 carbon black (Ptx(CeO2 NR)yCz) and evaluation of their electrocatalytic activity towards the oxygen reduction reaction (ORR), aiming the application of 4-electrons process in direct ethanol fuel cells (DEFCs). The hybrid electrocatalysts are characterized by X-ray diffraction (XRD), energy-dispersive spectroscopy (EDS), transmission electron microscopy (TEM), contact angle measurements and X-ray photoelectron spectroscopy (XPS), inductively coupled plasma mass spectrometry (ICP-MS), CO-stripping analysis and electrocatalytic activity for ORR studied by the rotating ring-disc electrode (RRDE) technique and single fuel cell experiments. The Ptx(CeO2 NR)yCz hybrid electrocatalysts prove to be efficient for ORR in a 4-electron process, maintaining a high conversion rate of O2 to H2O, even at reduced platinum (Pt) load. The electrocatalyst presents a notable an unusual behavior in single fuel cell experiments presenting slightly lower open circuit voltage than Pt based commercial electrocatalysts, containing Pt only, as well as improved current and power density. This is achieved at operating temperatures between 40 °C and 70 °C, making the material very promising for application in high efficiency low temperature fuel cells.
Keywords: ceria nanorods; direct ethanol fuel cells; oxygen reduction reaction; Vulcan XC-72